(untitled) (Research, Society and Development, 2022)
In economically emerging countries such as Brazil, sport fishing is emerging as an important social and economic contributor. However, despite its importance, some aspects still lack information, which jeopardizes the planning, mapping and proper management of the activity. Thus, the objective of this paper was to describe the socioeconomic profile of the sport fishermen of Itaipu Reservoir, Brazil, in order to provide subsidies for public and private investments in the promotion of regional fishing tourism. For this, semistructured socioeconomic questionnaires were given to sport fishermen (total respondents = 823 fishermen) participating in 19 sport fishing tournaments held at Itaipu Reservoir in 2015 and 2016. The majority of the fishermen that were interviewed were male (84%), married (65%), age 31-40 (31%) and had a high level of education (34%). The professional activities reported by the respondents were 43% entrepreneurs, 15% professionals, 15% public servants, 9% private sector workers and 7% students. The household income ranged from 3 to 6 times the Brazilian minimum wage (minimum wage R 954.00 = US 253.72, US 1 = R 3.76, October 2018) (34%). The expenditure on fishing events averaged US 140.33. The sport fishermen from Itaipu Reservoir demonstrated a high socioeconomic standard in relation to the fishermen from other regions of the country, which foments the local economy.